Why does global democracy not inspire explanatory research? Removing conceptual obstacles toward a new research agenda. (February 2020) - Agné, Hans
Democratic practices exist in politics within and beyond individual states. To date, however, it is only the democratic practices within states that have been analyzed in search for causal explanations of political outcomes, for example, peace and human rights protection. Having established the problematic nature of this situation, the purpose of this article is to explain why the situation emerges in political science and then to suggest a strategy to overcome it. The lack of attention to global democracy, or democracy beyond the state more generally, in explanatory theory is suggested to depend on prevalent but unnecessary conceptual delimitations of democracy which contradict standard assumptions about international politics. Those contradictions can be avoided, however, by defining democracy as rule by the largest group. It is argued that the concept of rule by the largest group, while protecting traditional virtues of democracy such as freedom and equality of individual persons in politics, allows scholars to describe a wider range of international practices than have been available for empirical research based on the dominating conceptions of democracy in normative and empirical literatures. Most fundamentally, it frees future research on the effects of democracy beyond the state from a key risk of self-contradiction.